This Changes Nothing: The Paris Agreement to Ignore Reality. Issue 6 (1st November 2016) - Spash, Clive L.
Abstract: At the 21st session of the Conference of the Parties to the United Nations Framework Convention on Climate Change held in Paris, France, 30 November to 11 December 2015, an Agreement was reached by the international community including 195 countries. The Agreement has been hailed, by participants and the media, as a major turning point for policy in the struggle to address human-induced climate change. The following is a short critical commentary in which I briefly explain why the Paris Agreement changes nothing. I highlight how the Agreement has been reached by removing almost all substantive issues concerning the causes of human-induced climate change and offers no firm plans of action. Instead of substantive cuts in greenhouse gas (GHG) emissions, as soon as possible, the intentions of the parties promise escalation of damages and treat worst-case scenarios as an acceptable 50:50 chance. The Paris Agreement signifies commitment to sustained industrial growth, risk management over disaster prevention, and future inventions and technology as saviour. The primary commitment of the international community is to maintain the current social and economic system. The result is denial that tackling GHG emissions is incompatible with sustained economic growth. The reality is that Nation States and international corporations are engaged in an unremitting and ongoing expansion of fossil fuel energy exploration, extraction and combustion, and the construction of related infrastructure for production and consumption. The targets and promises of the Paris Agreement bear no relationship to biophysical or social and economic reality.